The transcriptomic profile of endometrial receptivity in recurrent miscarriage. (June 2021) - Craciunas, Laurentiu; Pickering, Oonagh; Chu, Justin; Choudhary, Meenakshi; Žurauskienė, Justina; Coomarasamy, Arri
Abstract: Objective: To characterise the endometrial transcriptomic profiles of women who suffered recurrent miscarriage and to set the foundation for the development of an endometrial receptivity test that could predict the fate of subsequent pregnancies. Study design: This was a prospective multicentre cohort study performed at the Tommy's National Centre for Miscarriage Research in Birmingham, Saint Mary's Hospital in Manchester and Royal Devon & Exeter Hospital, United Kingdom. The study was conducted between December 2017 and December 2019. Endometrial biopsies were obtained during the window of implantation from 24 women aged 18–35 years, who were not pregnant and regularly menstruating, diagnosed with unexplained recurrent miscarriage by standard investigations as per the ESHRE guidelines. Exclusion criteria included risk factors such as smoking, obesity or hyperprolactinemia. The RNA transcripts abundances were quantified using Kallisto . R packages tximport and DESeq2 were used to summarize count estimates at the gene level and to analyse the differential gene expression. Results: Women who suffered four or more miscarriages had 19 differently expressed genes after adjustment for multiple comparisons. They were related to biological processes such as immunity ( HLA-DMA, CCR8, ALOX5 ), energy production ( ATP12A ), hormone secretion ( CGA ), adhesion ( CHAD, ADGRF2, AQP5, TBCD, CTNND1, NKD2 ) and cell proliferation ( NCCRP1 ). Based on 421 differently expressed genes, women who achieved a subsequent live birth displayed an enrichment of processes related to the regulation of cell structure and proliferation, and a depletion of processes related to immunity, trans-membrane transport and coagulation. Conclusions: Women in the extreme miscarriage cohort had a distinctive endometrial transcriptomic signature compared to women with low order miscarriages. There was a partial overlap with the transcriptome of asynchronous endometrium suggesting the endometrial factor to be a different entity in the context of recurrent miscarriage. Women who achieved a live birth in their subsequent pregnancy displayed an enrichment of genes related to the regulation of cell structure and proliferation, while women who suffered a subsequent miscarriage displayed an enrichment of genes related to immunity, trans-membrane transport and coagulation.